2011
DOI: 10.1051/0004-6361/201015690
|View full text |Cite
|
Sign up to set email alerts
|

An asteroseismic study of the O9V star HD 46202 from CoRoT space-based photometry

Abstract: The O9V star HD 46202, which is a member of the young open cluster NGC 2244, was observed by the CoRoT satellite in October/November 2008 during a short run of 34 days. From the very high-precision light curve, we clearly detect β Cep-like pulsation frequencies with amplitudes of ∼0.1 mmag and below. A comparison with stellar models was performed using a χ 2 as a measure for the goodness-of-fit between the observed and theoretically computed frequencies. The physical parameters of our best-fitting models are c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 46 publications
9
113
0
Order By: Relevance
“…Some conclusions from earlier applications get even strengthened in retrospect by the present work: e.g. on chemical tagging in order to determine population membership of hypervelocity stars (Przybilla et al 2008a;Tillich et al 2009), the investigation of subtle abundance signatures to constrain supernova nucleosynthesis from binary supernova runaways (Przybilla et al 2008b;Irrgang et al 2010), or on coupling quantitative spectroscopy with asteroseismic analysis of pulsating OB stars observed with CoRoT (Briquet et al 2011). And, the methodology offers a high potential for future applications, that may facilitate many more facets of astrophysics to be studied at high confidence.…”
Section: Discussionmentioning
confidence: 67%
“…Some conclusions from earlier applications get even strengthened in retrospect by the present work: e.g. on chemical tagging in order to determine population membership of hypervelocity stars (Przybilla et al 2008a;Tillich et al 2009), the investigation of subtle abundance signatures to constrain supernova nucleosynthesis from binary supernova runaways (Przybilla et al 2008b;Irrgang et al 2010), or on coupling quantitative spectroscopy with asteroseismic analysis of pulsating OB stars observed with CoRoT (Briquet et al 2011). And, the methodology offers a high potential for future applications, that may facilitate many more facets of astrophysics to be studied at high confidence.…”
Section: Discussionmentioning
confidence: 67%
“…Ribas et al (2000) used eclipsing binaries to show that α increases with mass, but Claret (2007) found that α = 0.2 could reproduce correctly the properties of 3 < M < 30 M stars. Using asteroseismology, Briquet et al (2007) determined α = 0.44 ± 0.07 for the B2IV star θ Oph and Briquet et al (2011) obtained α = 0.1 ± 0.05 for the O9V star HD 46202. One of the main reasons for these differences is that it is usually the extent of the convective core that is constrained from observations.…”
Section: The Main Sequence Widthmentioning
confidence: 99%
“…CoRoT observations show further examples of the variability of O stars and several frequencies in light curves were found, which were not predicted to be unstable modes by the OPAL and OP seismic models (cf. Blomme et al 2011;Briquet et al 2011;Degroote et al 2010;Mahy et al 2011).…”
Section: Oscillation Spectra Of Early-type Starsmentioning
confidence: 99%